The relationship between soft skills, self-efficacy, and career development among Malaysian generation Z - Che Amat, Muhammad Asyraf; Talhah, Haziq (Macrothink Institute, 2021)
Generation Z is the new generation that is entering the workforce in Malaysia. This generation will be the new major working people in Malaysia, which makes their career development an important topic. From the literature review, it was shown through many studies that Generation Z is aware of soft skills but lacks the practice of the said skills. However, they have remarkably high self-efficacy. Both soft skills and self-efficacy might influence Generation Z’s career development. This leads to the aim of this study on identifying the relationship between soft skills, self-efficacy, and career development among Generation Z in Shah Alam, Selangor, Malaysia. This study involved a total of 384 Generation Z in Shah Alam. This research employed a quantitative correlational and descriptive research design. Soft Skill Questionnaire was used to identify the respondents’ equipped soft skills and which soft skills they deemed important. Meanwhile, the self-efficacy variable was measured by using the General Self-Efficacy Scale. Lastly, career development was assessed using Career Development Assessment. Correlation analysis was used to test the relationship of variables involved. The results of the study showed that there was a relationship between soft skills, self-efficacy, and career development among Generation Z in Shah Alam. This study has implications for career counselling, counsellors, and Generation Z. Both soft skills and self-efficacy have influence on Generation Z’s career development massively.